Decision Support System Using the Application of Tahani Model Fuzzy Logic - Rahima, Rahima; Radhiah, Radhiah; Mahmudi, Mahmudi (Syiah Kuala University, 2024)
The fuzzy logic of The Tahani model is described as a model used to process data searches, only that this model is based on operations in fuzzy set theory to obtain information that matches its data search criteria. In this study, the fuzzy logic of the Tahani model was applied to help the company PT. Lambarona Sakti in terms of determining recommendations for reordering Honda motorcycles with linguistic criteria against vehicle data that has definite characteristics. The determination of the recommendation of the vehicle to be rebooked from the main dealer is carried out by first doing the fuzzification stage, then determining the degree of membership, then a data search will be carried out based on the desired criteria, the final stage is determined recommendation based on the resulting fire strength value. How the determination of the fire strength value works can be done using the help of the Microsoft Excel application and automatically the results will be in accordance with the filling of the membership degree that has previously been done. 2 possible recommendations were obtained, namely there are recommendation results with all types of Honda motorcycles to be reordered and there are recommendation results with only a few types of Honda motorcycles to be reordered.